Comparison of tagging in an educational context: Any chances of interplay?. (28th January 2010) - Vuorikari, Riina; Poldoja, Hans; Koper, Rob
Web-based tagging systems for educational resources allow users to associate free keywords with resources. This paper first studies similarities and differences of tagging systems that are an integrated part of learning platforms, and then introduces a case study on teachers' use of social tagging tools. Analysing more than 20, 000 teacher-created tags from five platforms, it was found that even if the tagging system designs differ, more than 30% of the posts were shared through tags between two or more platforms. Thus, tags can create interplay not only between the users and their tools, but also between diverse learning platforms.